A CFI algorithm for estimating the Doppler peak of wind-profiling radar. Issue 10 (3rd October 2022) - Neethu Mohan, M. C.; Samson, Titu K.; Paul, Binu; Rakesh, V.; Rebello, Rejoy; Pezholil, Mohanan
ABSTRACT: Wind profiling radars are very useful instruments in meteorological forecasting for evaluating the three dimensional wind velocities. The challenging part of this job is to identify the true Doppler peaks of atmospheric origin from a noisy Doppler profile. This paper presents a novel algorithm for the Doppler peak estimation in windprofilers. The normalized Doppler spectrum of each range bin is divided into multiple clusters and low signal to noise ratio (SNR) clusters are discarded. Then, clusters having no continuity along height axis are filtered out and finally the remaining clusters are interpolated to get the wind profile. The algorithm performs very well even when the signal SNR is consistently below −3 dB over successive range bins. The proposed algorithm is found to have improved performance compared to existing algorithms with a reduced computational time.